ANALYSIS OF ECONOMIC INDICATORS OF INNOVATIVE DEVELOPMENT OF ELECTRIC POWER COMPANIES - Y. Aleksandrov (Publishing House of the State University of Management, 2016)
The article analyzes the criteria for evaluating the innovative development of multi-functional electric power companies. It proposed to supplement the innovative development indicators, which will allow management companies to more objectively evaluate the status and prospects of innovative development in the economic systems of different hierarchical levels of energy companies, taking into account the cumulative effect of the most important factors influencing the effectiveness of innovation.